Clinical characteristics and treatment outcome in a large multicentre observational cohort of PDGFRA exon 18 mutated gastrointestinal stromal tumour patients. (May 2017) - Farag, Sheima; Somaiah, Neeta; Choi, Haesun; Heeres, Birthe; Wang, Wei-Lien; van Boven, Hester; Nederlof, Petra; Benjamin, Robert; van der Graaf, Winette; Grunhagen, Dirk; Boonstra, Pieter A.; Reyners, Anna K.L.; et al.
Abstract: Purpose: Patients, platelet-derived growth factor receptor alpha ( PDGFRA ) D842V-mutated gastrointestinal stromal tumours (GISTs) are known for their insensitivity to imatinib. However, in clinical practice responses have been observed in some patients. We describe the natural history and treatment outcomes in a cohort of PDGFRA exon 18 mutated GIST patients. Patients and methods: A retrospective cohort study was conducted in PDGFRA exon 18 mutation GIST patients treated in six expert centres in the Netherlands and the United States. Two independent radiologists assessed radiological response to imatinib according to Choi's criteria in all patients with measurable disease treated with imatinib in neo-adjuvant or palliative intent. Results: Seventy-one patients with PDGFRA exon 18 mutation were identified of whom 48 patients (69%) had a D842V mutation. Twenty-two (45.8%) D842V-mutated GIST patients received imatinib treatment, 16 had measurable disease. Fourteen out of the 23 (60.9%) patients with non-D842V mutations received imatinib treatment, eight had measurable disease. Two out of 16 (12.5%) D842V-mutated GIST patients had partial response, 3 patients (18.8%) had stable disease and 9 patients (56.3%) had progressive disease as best response. Two patients did not have follow-up computed tomography scans to assess response. Six out of 8 (75%) patients with non-D842V exon 18 mutations had partial response and two (25%) had stable disease as best response. Conclusion: Patients with D842V-mutated GISTs can occasionally respond to imatinib. In the absence of better therapeutic options, imatinib should therefore not be universally withheld in patients with this mutation. Highlights: In contrast to previous findings, few D842V-mutated gastrointestinal stromal tumours (GISTs) do respond to imatinib. GISTs harbouring other mutations in platelet-derived growth factor receptor alpha exon 18 do have a good response to imatinib. Imatinib should not be universally withheld in patients with a D842V-mutated GIST.